A new approach to investigate conductive anodic filament (CAF) formation. Issue 1 (2nd February 2015) - Zou, Ling Chunxian; Hunt, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe the development of an approach that uses a flexible substrate to investigate the mechanism of conductive anodic filament (CAF) growth and effect of different material and manufacturing variables. Design/methodology/approach – A new approach using a simulated test vehicle (STV) has been developed to study the CAF phenomena. The STV can be easily built under controlled conditions in the laboratory using different glass fibres and resin powder to investigate the effect of different variables separately on CAF. The advantage of the STV is that CAF can be formed in relatively short period in a controlled way, and CAF growth can be easily identified using a back-lighting under a microscope due to the thin flex material used as the test sample. Findings – STV has been used to investigate a number of effects on CAF formation: different glass fibres, reflow process, acid contamination in drilled holes, desmear process and glass bundle size. The results demonstrate that for finished fibres acid contamination (plating solution) at the electrode was necessary for CAF formation. However, for unfinished glass fibres (loom state and heat cleaned) CAF can be formed without acid contamination. The reflow process significantly increases CAF formation. Running an aggressive desmear process and using large glass fibre bundle also increased CAF formation. Originality/value – This new approach will be of benefit for printed circuit board (PCB) supplier to evaluate CAF performance on different resin systems and glass fibres to provide high CAF resistance quality PCBs. The test period (168 hours) would be much shorter than the traditional CAF testing (1, 000 hours).